The Key To Success For 'Kefi' Coffee Shop In The New Normal Era: An Analysis of Adaptive Strategies - Wilujeng, Aura Masdena Nur; Ambarwati, Rita (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2025)
Research aim: This study aims to analyze the implementation of adaptive strategies in Coffe Shop "Kefi" in terms of product quality, service quality, and facilities in timplementingthe new normal era in Sidoarjo Regency. Method: Using qualitative methods, data collection techniques with interviews, documentation and observation.  This research focuses on analyzing the adaptive strategies carried out by Coffee Shop "Kefi with SWOT Analysis. Data analysis includes data collection. Presentation of data, Conclusion Drawing, and Verification Research Finding: Adaptive Coffee Shop "Kefi" strategies to improve product quality include providing a delicious and varied menu of coffee and non-coffee drinks, preparing superior coffee quality, in the aspect of service quality, namely friendly, responsive service, and in the aspect of facilities provided are comfortable seating, a pleasant atmosphere, and attractive interior design, WiFi access, music played at Coffee Shop "Kefi" and the availability of clean and well-maintained toilets. Theoretical contribution: This research contributes to analyzing the way to build a model approach. This research can help coffee shops identify market trends and changes and adjust their strategies effectively to stay relevant and attract customers. Practical implication: In the café industry, adaptive strategies can be developed regarding product quality, service quality and facilities. Research limitation : This study is constrained by its focus solely on coffee shop environments